2013
DOI: 10.1016/j.clml.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

CXC Chemokine Receptor 4 Expression, CXC Chemokine Receptor 4 Activation, and Wild-Type Nucleophosmin Are Independently Associated With Unfavorable Prognosis in Patients With Acute Myeloid Leukemia

Abstract: BACKGROUND CXC chemokine receptor 4 (CXCR4) is activated by phosphorylation and is essential for migration of hematopoietic precursors to bone marrow. CXCR4 overexpression predicts unfavorable prognosis in patients with acute myeloid leukemia (AML). Nucleophosmin (NPM1) mutation is the most frequent genetic abnormality in AML patients and predicts a favorable prognosis. In vitro studies have suggested that mutant NPM decreases CXCR4-mediated chemotaxis by downregulating CXCR4, thereby linking the NPM and CXCR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 67 publications
1
12
0
1
Order By: Relevance
“…SLC7A11, a cystine-glutamate antiporter, is stabilized in the plasma membrane by CD44v8-10 through its interaction with and stabilization of X CT/SLC7A11 (27), while expression of Apart from transcription and protein translation, cell-surface expression of CXCR4 depends on its recycling and externalization on the cell membrane (33). PIM1-mediated phosphorylation of CXCR4 at S339 is necessary for its surface localization (34)(35)(36), and PIM1 is a known downstream target of BETP (37). Immunoblot analysis of OCI-AML3 cells treated with ARV-825 confirmed that PIM1 expression and the consequent phosphorylation of CXCR4 (S339) were decreased in the treated cells, while total CXCR4 protein expression remained unchanged ( Figure 3F).…”
Section: Arv-825 Inhibits Aml Cell Proliferation and Induces Apoptosismentioning
confidence: 99%
“…SLC7A11, a cystine-glutamate antiporter, is stabilized in the plasma membrane by CD44v8-10 through its interaction with and stabilization of X CT/SLC7A11 (27), while expression of Apart from transcription and protein translation, cell-surface expression of CXCR4 depends on its recycling and externalization on the cell membrane (33). PIM1-mediated phosphorylation of CXCR4 at S339 is necessary for its surface localization (34)(35)(36), and PIM1 is a known downstream target of BETP (37). Immunoblot analysis of OCI-AML3 cells treated with ARV-825 confirmed that PIM1 expression and the consequent phosphorylation of CXCR4 (S339) were decreased in the treated cells, while total CXCR4 protein expression remained unchanged ( Figure 3F).…”
Section: Arv-825 Inhibits Aml Cell Proliferation and Induces Apoptosismentioning
confidence: 99%
“…Stromal cell-derived factor-1 (SDF-1) is a small chemokine that regulates the mobilization, retention, migration, trafficking and homing of hematopoietic stem cells and lymphocytes (10,11). An increasing amount of evidence has indicated that chemotaxis signaling serves a crucial role in the migration of cancer cells (12)(13)(14)(15). Chemokines serve roles as signal initiators and are involved in changes of the actin cytoskeleton (16), which are required for cellular morphological changes and motility (17).…”
Section: Introductionmentioning
confidence: 99%
“…[21] In another study of 117 patients who were tested for NPM1 mutations by PCR, there was no correlation between CXCR4 expression and NPM1 mutation. [36] It has been reported that CXCR4 expression was significantly higher in FLT3-ITD AML than in FLT3/wt AML. [37] The possible mechanism was that FLT3-ITD may activate CXCR4 signaling, thereby further affecting the function of the SDF-1α/CXCR4 axis.…”
Section: Discussionmentioning
confidence: 99%